STRATEGI DIPLOMASI BUDAYA KOREA SELATAN TERHADAP JEPANG MELALUI MEDICAL TOURISM TAHUN 2009-2016 - Etfa, Yosuananda; Priadarsini, Ni Wayan Rainy; Intan Parameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research focuses on the strategy of cultural diplomacy carried out by South Korea. This study seeks to explain South Korea's cultural diplomacy efforts medical tourism in improving South Korea's diplomatic relations with Japan in 2009-2016. This research uses three concepts, namely: first, the concept of Cultural Diplomacy by Milton Cumming, Jr., which explains the steps taken by the state to influence other countries through cultural diplomacy. Second, the concept of Medical Tourism by John Connell explains what the definition of Medical Tourism and how Medical Tourism is a new form of Cultural Diplomacy, Thirdly, the concept of National Branding by Anholt which explains the importance of state brands in enhancing the image of the State in the international world. the three concepts illustrate what South Korea's strategy is for carrying out cultural diplomacy to Japan in an effort to improve diplomatic relations between South Korea and Japan. Keyword : Cultural Diplomacy, medical tourism, national branding